2015
DOI: 10.1186/s13059-015-0718-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of rare interphase chromosome breaks and translocations by high-throughput imaging

Abstract: We report a method for the sensitive detection of rare chromosome breaks and translocations in interphase cells. HiBA-FISH (High-throughput break-apart FISH) combines high-throughput imaging with the measurement of the spatial separation of FISH probes flanking target genome regions of interest. As proof-of-principle, we apply hiBA-FISH to detect with high sensitivity and specificity rare chromosome breaks and translocations in the anaplastic large cell lymphoma breakpoint regions of NPM1 and ALK. This method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Automated analysis of all images was performed based on a modified version of a previously described Acapella 2.6 (PerkinElmer) custom script [30, 3335]. This custom script performed automated nucleus detection based on the maximal projection of the DAPI image (ex.…”
Section: Methodsmentioning
confidence: 99%
“…Automated analysis of all images was performed based on a modified version of a previously described Acapella 2.6 (PerkinElmer) custom script [30, 3335]. This custom script performed automated nucleus detection based on the maximal projection of the DAPI image (ex.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the frequency of ETO-induced MLL fusions, we developed C-Fusion 3D, a highthroughput imaging-based methodology to probe chromosome breakage and rare translocations in individual cells with high sensitivity. Built upon the rationale of high-throughput break-apart fluorescence in situ hybridization (FISH) (Burman et al, 2015a;Roukos et al, 2013), C-Fusion 3D detects individual cells with chromosome breakage and/or fusions by measuring the extent of spatial separation or colocalization of individual chromosome breaks in 3D (Figure 2A). We found that C-Fusion 3D can detect individual cells with chromosome translocations at frequencies down to 10 -4 (data not shown).…”
Section: Mll Fusions Form Rarely In Hematopoietic Cell Lines and Progmentioning
confidence: 99%
“…FISH spots were identified in all channels in maximal projected images by using the spot detection algorithm C. Distances between all different spots of all different channels were calculated in 2D by using custom-made building blocks, while the z plane having the maximum pixel intensity of each spot was identified. Single cell information was then exported as text files and custom made scripts in R developed based on previous versions (Burman et al, 2015a), were used to calculate the Euclidean distances between different spots in 3D and to calculate frequencies of cells with chromosome breakage and/or translocations. Correction of shifts due to chromatic aberration in z was performed by defining the pairwise shifts in z between all the different channels measured on images of a stained genomic locus by FISH using a single BAC labeled with all different color fluorophores.…”
Section: C-fusion 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…Great strides have been made in the realm of high-content DNA FISH microscopy approaches (hiFISH), which utilize automated image acquisition and analysis tools to interrogate DNA probe libraries. 21,29,30 Potentially, this approach can accurately quantify gene pairing events that occur across larger linear genomic distances and between chromosomes at high-resolution but current highcontent microscopy experiments are still limited to only 4 distinct fluorophores for visualization (one of which must be dedicated to a nuclear stain for automated image analysis). Therefore, current methods are inadequate for the co-visualization of multiple genes in conjunction with co-detection of chromosome territories, sub-nuclear structures and/ or distinct epigenetic marks.…”
Section: Introductionmentioning
confidence: 99%